2007
DOI: 10.1177/0145445506297016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Errors, Anxiety Sensitivity, and Anxiety Control Beliefs

Abstract: This study examined the interrelations among negative cognitive errors, anxiety sensitivity, and anxiety control beliefs and explored their unique and specific associations with anxiety symptoms in a community sample of youth. Existing research has suggested that these constructs are related to childhood anxiety disorder symptoms; however, additional research is needed to test the interrelations among negative cognitive errors, anxiety sensitivity, and anxiety control beliefs and to determine if they show uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 54 publications
5
40
2
Order By: Relevance
“…Consistent with past findings linking anxiety sensitivity, behavioral inhibition, and interpretive and judgment biases to anxiety-related difficulties Rabian et al, 1999;Weems et al, 2007), findings from this study showed that all four risk factors were interrelated, and that higher anxiety problems were associated with higher levels of each of these factors. Extending extant literature in this area, however, the present study sought to examine these putative risks factors in tandem, examining the ways in which they influence anxiety problems.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with past findings linking anxiety sensitivity, behavioral inhibition, and interpretive and judgment biases to anxiety-related difficulties Rabian et al, 1999;Weems et al, 2007), findings from this study showed that all four risk factors were interrelated, and that higher anxiety problems were associated with higher levels of each of these factors. Extending extant literature in this area, however, the present study sought to examine these putative risks factors in tandem, examining the ways in which they influence anxiety problems.…”
Section: Discussionsupporting
confidence: 90%
“…Anxiety problems have been found to be associated with a number of putative risk factors, including biologically-based anxiety precursors, such as anxiety sensitivity (Schmidt et al, 1997) and behavioral inhibition (Muris et al, 2003), and cognitive risk factors, such as interpretive and judgment biases (Rapee et al, 1996;Weems et al, 2007). Less is known, however, about the interrelations of these factors in the risk for anxiety, or how these factors covary to influence anxiety problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on AS in youth have considered comorbidity and examined symptom specificity, with contradictory findings. For example, some studies have found relations between AS and anxiety while controlling for depression, but not the reverse (i.e., AS was not related to depression symptoms after controlling for anxiety; Allan et al 2014;Joiner et al 2002;McLaughlin and Hatzenbuehler 2009;Muris et al 2001;Weems et al 2007). In contrast, others have found AS was related to depression after controlling for anxiety (e.g., Weems et al 1997).…”
mentioning
confidence: 99%
“…The CASI has good internal consistency (Cronbach's alpha = .87) and good 2 week test-retest reliability with clinical and nonclinical samples [.76 and .79, respectively;Silverman et al (1991)]. Other analyses of test-retest reliability indicate r = .48 with a 6 month window between testing (Ginsburg and Drake 2002) and r = .48 with a 1 year window between testing (Weems et al 2007). Cronbach's alpha coefficients in the present study were .88 at T1 and .86 at T2.…”
Section: Anxiety Sensitivitymentioning
confidence: 99%